Ethnomathematics on the Saluang: Analysis of mathematical concepts in Minangkabau musical instruments - Rahmi, Fathur; Sofi Yonalta; Intan Rozana (Universitas Hamzanwadi, 2025)
Saluang musical instruments are unique during manufacturing because they contain mathematical concepts. However, no one has further realized and studied the mathematical concepts of musical instruments. This study aims to explore the relationship between mathematics and Saluang. The results of the exploration are fascinating because mathematical concepts such as arithmetic and geometric series are the most important ones applied during the Saluang manufacturing process. It will also be fascinating to apply in learning to motivate students to learn. The research method used is ethnography. Data were obtained from direct observation, interviews, literature reviews, and documentation. The results obtained from this study are that during the Saluang manufacturing process, there are cultural values ​​and mathematical concepts that include geometry and arithmetic series. Using leaves, cloth, and fingers to determine the distance between holes in making Saluang is a unique mathematical concept. This research can be used as a guideline for teachers in compiling learning devices by paying attention to activities that are very close to students.